Power output demands of womens world cup road cycling - Trewin, C. B.; Martin, D. T.; McLean, B. D.; Lee, H.; Lawton, E. W.; Victor, J. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Power output (PO) associated with women`s road cycling racing is poorly described. The purpose of this study was to characterise the PO demands during Womens World Cup (WC) road cycling competition and to compare PO requirements for a top 20 placing (TOP20) versus a non-top 20 placing (NONTOP20). PO data were collected using SRM cranks from eight Australian women road cyclists (mean± SD: 22.8± 4.4 yrs, 166.8± 4.3 cm, 58.0± 1.7 kg, max 3.61± 0.24Lmin-1) during rounds 1 and 2 of the Women`s Elite WC 1999. Four women were monitored in one race only and four women in both races, resulting in 12 separate race PO profiles. Both races were held over similar courses (102-102.6 km, 18-20 laps, maximal elevation variation 30m) and average PO between the two races were not different, therefore, all profiles were pooled for further analysis (Round 1=189.7± 17.0W, Round 2=189.6± 18.9W). Five TOP20 and seven NONTOP20 race PO profiles were collected. An average power distribution was developed describing the % of total race time spent in 0.75 W.kg-1 power bands, ranging from <0.75 to >7.5W.kg1. Non-paired t-tests were used to compare TOP20 with NONTOP20, and WC placing was correlated to PO data. Based on group data (N=12), WC races had the following characteristics: 169± 2.5min, 28± 21 place (range 1st-57th), 3.3± 0.3 W.kg-1 average PO, 13.8± 2.6 W.kg-1 POpeak. 27± 4% of race time was spent in the <0.75 W.kg1 power band and 9± 3% of race time was spent in the >7.5 W.kg-1 power band. No more than 10% of race time was accumulated in any other power band. Differences in PO between TOP20 and NONTOP20 were only significant in the lowest and highest PO intervals. TOP20 spent more time >7.5 W.kg-1 (11± 2 vs 7± 2%, P<0.01), and less time < 0.75 W.kg-1 (24 ± 4 vs 29± 3%, P<0.05). Additionally, TOP20 produced higher average PO (3.6± 0.4 vs 3.1± 0.1 W.kg-1, P<0.01). There was a strong association between WC placing and average PO (r= -0.73, P<0.01) and also between WC placing and time >7.5 W.kg-1 (r= -0.79, P<0.01). These data demonstrate a significant association between PO and competition performance, and indicate that top 20 placed cyclists (those who gained WC points) are spending more time in the highest power band.